Analysis of Driving and Inhibiting Factors of Literacy Activities at Islamic Elementary School - Ayu Nitami (IAIN Surakarta, 2023)
Literacy activities are important for students because they can improve critical thinking skills, creativity, and other thinking skills. The GLS program was established to help improve student literacy activities in schools. This study aims to determine the driving and inhibiting factors of literacy activities in MIN 4 Sukoharjo. This research uses a qualitative approach. The subjects in this study were teachers. In comparison, the informants in this study were the principal and students. Data is collected through observation, interview and documentation techniques using observation sheet instruments and interview guidelines. Data analysis techniques carried out include four stages, namely the stages of data collection, data reduction, data presentation, and conclusions. The study results show that the success of implementing literacy activities is influenced by supporting factors from schools, students, parents and the role of teachers as facilitators of literacy activities in schools. Inhibiting factors that affect the implementation of literacy activities come from students' lack of awareness to implement literacy activities, the availability of facilities in schools, the lack of teachers' ability to implement good and correct literacy activities, and the lack of cooperation between schools and parents